Optimal design of blended composite laminate structures using ply drop sequence. (January 2016) - Yang, Junbo; Song, Bifeng; Zhong, Xiaoping; Jin, Peng
Abstract: In this paper, the concept of ply drop sequence (PDS) is introduced for designing of composite laminate structures with multiple regions. The PDS describes the order of ply-drops from the thickest guide laminate to a series of thinner ones, and further ensures laminate continuity across the entire structure. Comparing with deleting a contiguous innermost/outermost plies in the classical guide-based blending, using PDS is more flexibly of dropping plies between adjacent regions. A fully blended design is represented by a stacking sequence of the guide, a PDS and a thickness distribution over the whole regions of the structure. A genetic algorithm (GA) with special operators and codification is adopted for the PDS-based blending optimization, which guarantees the design is completely blended within the GA iterations. The proposed method is applied to an 18-panel horseshoe benchmark problem to demonstrate its flexibility and potentiality.